1978
DOI: 10.1007/bf00388629
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ammonium ions on uptake of glutamine and other amino compounds by cultured cells of rapeseed

Abstract: Nitrogen starvation for 24 h, particularly NH 4 (+) deprivation, of cultured repeseed (Brassica napus L.) cells caused them to develop the potential for a rapid increase in the rate of uptake of several amino compounds. Time-course studies, primarily using [(14)C]glutamine, showed that the increase in uptake rate continued for about 10 h after the 24-h N-starvation period. Addition of 2 mM NH 4 (+) to N-starved cells caused the increase in glutamin-uptake rate to cease, and the rate began to fall after 3-6 h t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In soybean and rapeseed cell suspension cultures nitrogen starvation leads to an increased uptake of amino acids (8,9), indicating derepression. Sucrose uptake by cotyledons of Ricinus communis is subjected to feedback inhibition by internal sucrose (10).…”
Section: Resultsmentioning
confidence: 99%
“…In soybean and rapeseed cell suspension cultures nitrogen starvation leads to an increased uptake of amino acids (8,9), indicating derepression. Sucrose uptake by cotyledons of Ricinus communis is subjected to feedback inhibition by internal sucrose (10).…”
Section: Resultsmentioning
confidence: 99%
“…1-4, [11][12][13][15][16][17][18]. Leucine was selected as the first amino acid to be tested; it comprises about 7% of all amino acid residues in the main reserve protein, hordein (10), and is generally metabolized slower than most amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…However, when rapeseed or soybean cells are cultured in suspension in the presence of NH4NO3, they take up amino acids, e.g. glutamine and leucine, very slowly (9,10). When the cells are transferred to a medium without nitrogen nutrients, their capacity for uptake of many amino acids increases several-fold in 24 h. The authors suggested that one possible explanation for the inhibition caused by NH4NO3 is that NH4' increases the intracellular concentration of glutamine, which would then inhibit amino acid uptake through transinhibition (9).…”
Section: Discussionmentioning
confidence: 99%
“…glutamine and leucine, very slowly (9,10). When the cells are transferred to a medium without nitrogen nutrients, their capacity for uptake of many amino acids increases several-fold in 24 h. The authors suggested that one possible explanation for the inhibition caused by NH4NO3 is that NH4' increases the intracellular concentration of glutamine, which would then inhibit amino acid uptake through transinhibition (9). It is quite possible, however, that amino acid uptake in these cells is regulated by a repression-like mechanism similar to that in the barley scutellum.…”
Section: Discussionmentioning
confidence: 99%